2016
DOI: 10.1002/eat.22513
|View full text |Cite
|
Sign up to set email alerts
|

Family‐based therapy for young adults with Anorexia Nervosa restores weight

Abstract: FBTY for young adults with AN and atypical AN, which involves support adults participants have chosen, results in weight restoration that is sustained up to a year after treatment. © 2016 Wiley Periodicals, Inc. (Int J Eat Disord 2016; 49:701-707).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 17 publications
(23 reference statements)
0
24
0
1
Order By: Relevance
“…An open trial of TAY-FBT has recently shown promising outcomes for individuals with AN (Dimitropoulos et al, 2018). Another pilot study of FBT for young adults, which had a similar collaborative approach, has also shown promise (Chen et al, 2016).…”
Section: Balance Self-management With Caregiver-supportmentioning
confidence: 99%
“…An open trial of TAY-FBT has recently shown promising outcomes for individuals with AN (Dimitropoulos et al, 2018). Another pilot study of FBT for young adults, which had a similar collaborative approach, has also shown promise (Chen et al, 2016).…”
Section: Balance Self-management With Caregiver-supportmentioning
confidence: 99%
“…In a small study, 22 patients with AN between the ages of 18 and 26 years participated in a 6-month open trial of FBT for young adults (FBT-Y) 41. Patients started treatment at a mean body mass index (BMI) of 17.84.…”
Section: Empirical Evidence For Family-based Treatment For Anmentioning
confidence: 99%
“…AN can make them feel guilty or anxious which is neither justified nor helpful. Family therapy for AN can tackle these feelings, can identify interpersonal difficulties maintaining the disorder, teach psychosocial and communication skills, and thus enable the carers to help the patients work towards recovery [7,8]. The carers' help may also include supporting psychopharmacological treatment.…”
Section: Carers' Help For Patients With Anorexia Nervosamentioning
confidence: 99%